Improving children and adolescents’ quality of life, personal growth, well-being, and safety through health-behavioral education: a pre-post intervention study - Leung, Czarina; Leung, Tim; Lau, Daphne; Ng, Rachel; Fatin, Shahira; Chutke, Shelly; Pui, Cayla; Dai, Jing Xi; Yu, Josephine; Jia, Jason (Frontiers in Public Health, 2025)
IntroductionHong Kong children and adolescents are living with alarming deterioration of mental health and escalating risks of violence and self-harm. Self-value, Empower, Educate, and Protect from Dangers (SEED) health-behavioral education provided to children, caregivers, and care service providers by Be Priceless is the only Hong Kong program that integrates safety with mental, physical, and social well-being.Methods526 children aged 6 to 17 years were recruited into a pre-post intervention study from May 2021 to September 2024. The impact of our SEED health education intervention was evaluated on four outcome measures: health-related quality of life, emotional regulation, well-being/resilience, and safety.ResultsRelative to pre-course baseline, all four measures showed significant improvements after intervention which persisted for 6 months, with large effect sizes (Cohen’s d = 0.66–0.92, all p < 0.001), and especially for those who were ethnic minorities or with special education needs.DiscussionThese results provide evidence that the SEED health education of Be Priceless is an efficacious intervention that improves children’s well-being and safety, while promoting health equity and inclusivity in Hong Kong.